PROTECTION OF MINORITY SHAREHOLDERS FROM FRAUD IN LIMITED LIABILITY COMPANY DIVIDEND DISTRIBUTION - Hartanto, Stefanie (Lex Prospicit, 2024)
This research investigates the potential fraudulent actions carried out by majority shareholders and other corporate organs in the context of stock distribution. The primary focus is on the continuity of practices that may disadvantage minority shareholders and undermine the legal protections they should receive. Majority shareholders, often wielding significant influence in the General Meeting of Shareholders (RUPS), may exploit their power to manipulate decisions related to stock distribution. The presence of a quorum that can be achieved without the participation of minority shareholders increases the risk of fraud in this process. The aim of this research is to identify various fraudulent actions that may occur in stock distribution by majority shareholders and related corporate organs. Using a legal analysis approach and case studies, this research also explores ways in which minority shareholders might prevent or respond to fraudulent actions. Furthermore, the research examines the extent to which Law No. 40 of 2007 concerning Limited Liability Companies (UU PT) provides a legal basis to prevent and respond to fraudulent actions in stock distribution. Practical implications of potential fraud are analyzed to provide recommendations that can strengthen legal protections for minority shareholders. This research is expected to contribute to a deeper understanding of the dynamics of fraud in stock distribution, outline the legal challenges faced by minority shareholders, and formulate concrete steps to prevent and respond to such fraud in companies.